1964
DOI: 10.2466/pr0.1964.14.3.831
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Behavior and Curiosity in Two Age and Ability Groups of Children

Abstract: Sixty-four second and sixth grade children with IQs in the average and gifted ranges (1) were observed in a semi-structured situation with six selected objects and (2) were allowed to expose as frequently as they wished each of a series of slides varying in complexity. Exposure time was set at 0.20 sec. Analysis of variance applied to exploratory time during the observation period yielded significant results across objects, but not for the ability and age (school grade) variables. However, tachistoscopic expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1966
1966
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The position of Nunnally and Lemond (1973) leads to the expectation that older children are more curious than are younger children because older children probably have more information conflict to resolve than do younger children. A few experimenters (Hutt & McGrew, 1969;Pielstick & Woodruff, 1965 have shown that young children manifest more curiosity than do older children. Other experimenters (Kaess & Weir, 1968;Thomas, 1966) have failed to find significant differences in curiosity as a function of age.…”
mentioning
confidence: 99%
“…The position of Nunnally and Lemond (1973) leads to the expectation that older children are more curious than are younger children because older children probably have more information conflict to resolve than do younger children. A few experimenters (Hutt & McGrew, 1969;Pielstick & Woodruff, 1965 have shown that young children manifest more curiosity than do older children. Other experimenters (Kaess & Weir, 1968;Thomas, 1966) have failed to find significant differences in curiosity as a function of age.…”
mentioning
confidence: 99%
“…Welker [58] found that 7to 8-year-old chimpanzees showed less interest in his test objects than did 3to 4-year-old animals. Both Maw and Maw [38] and Pielstick and Woodruff [54] found evidence for higher ability children to be more curious. What is effective in arousing curiosity in elementary school children may be quite different from what is effective for college subjects.…”
Section: Curiosity and Science Education 811mentioning
confidence: 99%
“…According to Berlyne, "perceptual curiosity" [5,6] [54] have distinguished between "exploratory behavior" and "curiosity." The former term is used to describe interest in or attention to one portion of the environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation